2002
DOI: 10.1046/j.1464-410x.2002.02917.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered cognitive function in men treated for prostate cancer with luteinizing hormone‐releasing hormone analogues and cyproterone acetate: a randomized controlled trial

Abstract: Objective To report the first systematic investigation of the cognitive effects of luteinizing hormone-releasing hormone (LHRH) analogues in male patients, as LHRH analogues have been associated with memory impairments in women using these drugs for gynaecological conditions. Patients and methods Eighty-two men with extraprostatic prostate cancer were randomly assigned to receive either continuous leuprorelin, goserelin (both LHRH analogues), cyproterone acetate (a steroidal antiandrogen) or close clinical mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
158
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(173 citation statements)
references
References 24 publications
3
158
0
7
Order By: Relevance
“…[21][22][23][24][25][26][27] All adverse events associated with perprotocol treatment are shown in Table S3 in the Supplementary Appendix. The early diagnosis of failure of definitive treatment, as determined according to the PSA level, subjects otherwise asymptomatic men to many years of androgen deprivation, adversely affecting their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] All adverse events associated with perprotocol treatment are shown in Table S3 in the Supplementary Appendix. The early diagnosis of failure of definitive treatment, as determined according to the PSA level, subjects otherwise asymptomatic men to many years of androgen deprivation, adversely affecting their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal challenges in men via administration of luteinising hormone-releasing hormone agonists, such as leuprolide or goserelin, also may adversely affect hippocampal function through these hormonal channels. There are inconsistent findings with regard to the safety profile of androgen ablating agents, with some authors reporting no evidence of neurocognitive decline or neurobehavioural dysfunction (Salminen et al, 2003), and others finding impaired memory, attention, and executive function (Green et al, 2002).…”
Section: Hormonal Therapymentioning
confidence: 99%
“…Low testosterone levels may, in fact, alter serotonin neurotransmission [8], negatively affecting mood as demonstrated in animal models [9]. Also, testosterone deficiency may decrease cerebral perfusion in the brain regions involved in memory, reasoning, judgment, and emotions [10], leading to a deterioration in mental and overall wellbeing [11,12]. Studies in elderly subjects and non-cancer patients have reported a clear association between testosterone levels and depressive symptoms [13]: lower testosterone levels in older men have been associated with more depressive symptoms [14,15], which seem to disappear with testosterone hormone treatment [16,17].…”
Section: Introductionmentioning
confidence: 99%